2011
DOI: 10.1007/s00535-011-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between endocytoscopy and conventional histopathology in microstructural features of ulcerative colitis

Abstract: Our novel ECSS has good predictive value for the histopathological activity of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…Employing an approach similar to that used in the present study, Bessho et al [15] have shown the benefits of classifying the histological activity of UC using EC. In their report, the shape and distance of the crypt were also assessed, and an excellent correlation was revealed between EC and histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Employing an approach similar to that used in the present study, Bessho et al [15] have shown the benefits of classifying the histological activity of UC using EC. In their report, the shape and distance of the crypt were also assessed, and an excellent correlation was revealed between EC and histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, their study had some limitations because the EC observations required pretreatment with methylene blue or toluidine blue staining. The additional time required for EC observation was reported to be approximately 20 min in one area [15] . Therefore, a more practical procedure for assessing the histological activity of UC is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bessho et al proposed a scoring system based on the sum of graduated criteria including shave of the crypts graduated (0-3), distance between crypts (0-2) and the visibility of superficial microvessels (0-1). The Endocytoscopy System Score (ECSS) shows a strong correlation with histology and good agreement for distinguishing between active and inactive US [35]. These results were confirmed by Maeda et al who evaluated the performance of virtual chromoendoscopy coupled with endocytoscopy (CE-NBI) compared to standard endoscopy in UC [36].…”
Section: Journal Of Clinical Gastroenterology and Hepatology Issn 257mentioning
confidence: 73%
“…Previously, we reported that EC exceeds the diagnostic ability of both PIT and NBI-ME. [13][14][15][16] During EC, the ultra-magnified microvessels of the lesion can be observed, and they have been used to evaluate the inflammation grade of ulcerative colitis, 17 but there is little literature describing ultra-magnified microvessels in conjunction with colorectal neoplasm diagnoses. This pilot study investigated the ultra-magnified microvessel findings of colorectal lesions and compared their diagnostic ability with that of other modalities (eg, NBI-ME, PIT, and EC).…”
mentioning
confidence: 99%